Design Analysis of Remotely Amphibian Vehicle (RAV) –Underwater Drone - Kasno, Mohammad ‘Afif; Mohd Aras, Mohd Shahrieel; Keong, Yeoh Eik; Ab Azis, Fadilah; Mohamed Kassim, Anuar; Harun, Mohamad Haniff; Mohd Zambri, Mohd Khairi; Khamis, Alias (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
This project is mainly focusing on the conceptual design and design analysis of the Remotely Amphibian Vehicle (RAV). RAV is considered as an underwater drone or vehicle that can operate autonomously or remotely controlled by a user. The term “amphibian” is referring to a vehicle that is capable of functioning in dual environments, which is in aerial and aquatic. In order to meet that purpose, the ability of flying and submerging are implemented into this RAV. This innovation mends to assist and help human in aquatic operation as well as aerial activity. However, this is still a very recent concept with numbers of limitation and challenge. Challenges like transition in medium has limited and affected the performance of the vehicle in terms of flying capability or submerging ability. Available model in the market is either robust in flying such as quadcopters but imperfect in submerging and vice versa. Hence, this research is to study and analysis of the conceptual design a remote control amphibian vehicle that can fly and submerge models. In order to overcome the challenge mentioned above, denser material is preferable for body frame fabrication. Besides, a body design with low volume is recommended to achieve a better performance in transition medium. To judge the performance of the conceptual design, a series of simulations using SolidWorks will be carried out. At the end of this project, the design will be used to development a remotely amphibian vehicle that operate robustly in two mediums.